Unravelling and quantifying the aging processes of commercial Li(Ni0.5Co0.2Mn0.3)O2/graphite lithium-ion batteries under constant current cycling. Issue 1 (23rd November 2022) - Guo, Jia; Jin, Siyu; Sui, Xin; Huang, Xinrong; Xu, Yaolin; Li, Yaqi; Kristensen, Peter Kjær; Wang, Deyong; Pedersen, Kjeld; Gurevich, Leonid; Stroe, Daniel-Ioan
Abstract : Constant current charging and discharging is widely used nowadays for commercial lithium (Li) ion batteries (LIBs) in applications of portable electronic devices and electric vehicles. Abstract : Constant current charging and discharging is widely used nowadays for commercial lithium (Li) ion batteries (LIBs) in applications of portable electronic devices and electric vehicles. However, the main battery degradation mechanism during constant current cycling remains unclear. In this work, electrochemical cycling, real-time temperature monitoring, and operando electrochemical impedance spectroscopy of a fresh and an aged battery have been carried out to unveil the aging mechanism during constant current cycling. The results of the incremental capacity analysis (ICA) indicate that polarization is the main reason for the capacity fading during operation. Besides, post-mortem analysis of the electrodes reveals that the formation of a solid–electrolyte interphase (SEI) and cathode–electrolyte interphase (CEI) is the leading cause of electrode degradation. The interface formation and evolution over cycling (including thickening and chemical variation) leads to continuous loss of active materials. The presence of a SEI and CEI also increases the impedance for charge transfer and transport and reduces the kinetics of electrochemical Li-ion redox on the electrodes. Moreover, the irreversible Li loss due to Li plating and SEI formation has been quantified, which accounts for 16.8% of the total Li in the battery. This work provides a mechanistic understanding of the degradation mechanism of commercial LIBs, guides the rational design of commercial batteries and inspires the design of charging and discharging protocols toward enhanced cycling stability and prolonged cycle life.